Acute effects of blood flow restriction on muscle performance and fatigability using Mosso’s Ergography in young adults - Gautam, Kalyan; Khakurel, Gita; Kumar Karki, Prabin (Journal of Chitwan Medical College, 2025)
Introduction: Upon contraction, skeletal muscles produce force and power. When contractions are sustained, relative reduction in force and power is observed, a phenomenon termed muscle fatigue. This study aimed to evaluate muscle function and fatigability among young adults along with blood flow restriction using Mosso’s ergography. Method: A prospective repeated-measures study was carried out between 13 Apr and 05 Oct 2023 on healthy students of first-year undergraduates at Kathmandu Medical College. Ethical approval was obtained. Census sampling was used. Participants pulled 2 kg load under no occlusion, venous occlusion and arterial occlusion. Repeated measures were taken for work done (joules) and fatigue onset time (seconds) using Mosso's Ergograph. Statistical analysis was conducted using R Studio (version 4.2). Regression analysis was performed for correlations of muscle function with age, sex, body mass index, and blood pressure. A p≤0.05 was considered significant. Result: Out of 120 participants, males were 61(51%), average BMI 22.36±2.65 kg/m², mean systolic and diastolic BP 113±8 mmHg and 74±6 mmHg. Work done dropped from 34.8 joules (no occlusion) to 30.8 joules (venous occlusion) and 23.8 joules (arterial occlusion). Fatigue onset time fell from 144 seconds (no occlusion) to 131 (venous occlusion) and 107 (arterial occlusion). Sex and BMI significantly influenced outcomes, females showing 4.7% higher work done under venous occlusion (p=0.01) compared to males, and underweight individuals experiencing delayed fatigue onset (p=0.012). Conclusion: This study demonstrated the impact of altered blood flow on muscle performance and fatigability. Sex and BMI influenced muscle function.